Knowledge Sharing Using Social Media Platforms in Improving Academic Performance of Undergraduate Students at Tai Solarin University of Education - Quadri, Monsuru Omotayo; Osoba, Monisola A. (MiddleBelt Journal of Library and Information Science, 2020)
This study examined how knowledge sharing through the use of social media platforms has influenced the academic performance of undergraduate students, and to investigate the extent to which knowledge sharing on these platforms has improved their academic performance. The study was carried out at Tai Solarin University of Education. The survey research design was adopted. Subjects were drawn from the Tai Solarin University of Education, using the simple random sampling technique and purposive sampling. Research questions and hypotheses were formulated to guide the study. The sample comprised of 200 students, and questionnaire was used to collect data, which were analyzed by use of qualitative and quantitative techniques. The findings revealed that a great number of students in Tai Solarin University of Education had access to the internet. Also, there is no statistically-significant difference in the use of social media application between the male and the female in improving their academic performance. Finally, positive influence is significantly more than the negative influence of the usage of social media application on students’ behavior. The study recommended that social media websites be created for strict educational purpose to create a balance between social networking and academic work of students to guide against unnecessary failure in the academic performance of undergraduate students.